Green Economy And Its Role In Preventing Air Pollution In Major Cities - Nortozhiev Jahongir Muhammad ugli; Turabov Navruz Norjigit ugli; Rakhimova Durdona Zhurakulovna (Euro Asian Journal Publishing, 2024)
Air pollution is one of the most pressing and pressing problems of our time, which requires immediate solutions [1,2]. According to the World Health Organization (WHO), air pollution is responsible for more than 7 million deaths per year, as well as many chronic diseases such as asthma, bronchitis, lung cancer and cardiovascular diseases[3,4]. Most air pollution occurs in large cities, where more than half the world's population lives. In these cities, concentrations of particulate matter (PM 2.5) and ozone (O3) exceed safe levels recommended by WHO. This poses a serious threat to the health of residents, as well as the economy and the environment. Therefore, it is necessary to develop and implement effective strategies to combat air pollution that take into account not only the technical, but also the social, political and cultural aspects of the problem
Keywords: the green economy; air pollution; renewable energy